A Systematic Review of Literature on Factors Influencing the Effect of Fintech on Green Finance in ASEAN countries - Shaharuddin, Shahrin Saaid; Mahdzan, Nurul Shahnaz; Ismail, Izlin; Tareq, Mohammad Ali (Journal of Posthumanism, 2025)
Green finance, defined as financial actions aimed at supporting sustainable environmental practices, has emerged as a critical element in the fight against climate change and the promotion of sustainable development. In this context, fintech—short for financial technology—has become increasingly recognized as a transformative force that enhances the efficiency, accessibility, and scalability of green finance. This systematic literature review investigates the factors influencing the relationship between fintech and green finance, with a focus on three main aspects: moderating, mediating, and control variables in the context of ASEAN countries. The review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)methodology to explore the role of fintech in advancing green finance. Drawing from an extensive dataset of 5,508 publications published between 2020 and 2025, we analyse the factors that influence the effect of fintech on green finance—specifically the moderating, mediating, and control variables—using bibliometric analysis of 68 closely related journal articles. This review proposes a theoretical framework that examines how fintech facilitates green finance and provides empirical evidence that informs policymakers and directs future research aimed at integrating fintech and green finance within a unified framework.